Nursing Care for Cancer Patients with Chemotherapy Induced Anemia - Janthathai, Aphantree (Thai Red Cross Nursing Journal, 2023)
Chemotherapy-induced anemia is a common complication in cancer patients and a major cause of mortality and disability in cancer patients. Chemotherapy inhibits red blood cell formation and growth, and inhibits erythropoietin hormone synthesis in kidneys, thereby causing anemia. Some patients with severe anemia may delay chemotherapy or postpone treatment, which affects the outcomes of the treatment. As nurses are health personnel who play a major role in caring for cancer patients with chemotherapy-induced anemia, knowledge and an understanding of the pathophysiology of chemotherapy-induced anemia, its diagnosis and treatment are needed for nurses to care for patients with chemotherapy-induced anemia; with this care, patients will be safe from potential serious complications and continually receive chemotherapy according to the treatment plan.